DDIT4 mediates the proliferation-promotive effect of IL-34 in human monocytic leukemia cells. Issue 2 (April 2021) - Lv, Xiaoqian; Hu, Yuting; Wang, Lina; Zhang, Dongyue; Wang, Hao; Dai, Yibo; Cui, Xiaoxi; Zheng, Guoguang
Abstract : Abstract: Interleukin 34 (IL-34) is a cytokine that shares the receptor with colony-stimulating factor 1 (CSF-1). IL-34 is involved in a broad range of pathologic processes including cancer. We previously demonstrated that IL-34 promoted the proliferation and colony formation of human acute monocytic leukemia (AMoL) cells. However, the mechanism has not been elucidated. Here, by analyzing the gene profiles of Molm13 and THP1 cells overexpressing IL-34 (Molm13-IL-34 and THP1-IL-34), upregulation of the DNA damage-inducible transcript 4 (DDIT4) was detected in both series. Knockdown of DDIT4 effectively inhibited the proliferation, promoted apoptosis and colony formation in Molm13-IL-34 and THP1-IL-34 cells. Our results suggest that DDIT4 mediates the proliferation-promotive effect of IL-34 whereas does not mediate the promotive effect of IL-34 on colony formation in AMoL cells.